2017
DOI: 10.1002/jpln.201700046
|View full text |Cite
|
Sign up to set email alerts
|

Is glomalin an appropriate indicator of forest soil reactive nitrogen status?

Abstract: In this paper we address total glomalin‐related soil protein (T‐GRSP) as a possible indicator of differences in forest soils related to reactive nitrogen and forest composition. We focused especially on the relationship between T‐GRSP (g kg−1), soil organic carbon (SOC), and reactive nitrogen (Nr) availability among different categories of temperate forests and different horizons. Our study included 105 sampling sites divided into 5 categories, which vary in elevation and tree species composition (coniferous, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
3
7
0
Order By: Relevance
“…(r = 0.81). This direct relationship between the levels of glomalin and SOC has already been observed in soils under tree canopies (Vasconcellos et al 2016;Rotter et al 2017;Zang et al 2017). The relationship between The elements P, K, Na, Cu, Fe, Mn and Zn were extracted with Mehlich-1; Ca and Mg were extracted with KCl (mol L -1 ).…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…(r = 0.81). This direct relationship between the levels of glomalin and SOC has already been observed in soils under tree canopies (Vasconcellos et al 2016;Rotter et al 2017;Zang et al 2017). The relationship between The elements P, K, Na, Cu, Fe, Mn and Zn were extracted with Mehlich-1; Ca and Mg were extracted with KCl (mol L -1 ).…”
Section: Resultssupporting
confidence: 55%
“…The leaf litter deposition and the microenvironments in the vegetation coverage under these last two species may be favorable to AM fungi activity, microorganisms responsible for the production and deposition of glomalin in the rhizosphere. It is also possible that the quality of the leaf litter affected the decomposition rates of the organic matter, corroborating Joly et al (2017), as well as the glomalin content (Rotter et al 2017) in the soil. Silva et al (2014) noted some factors which could be related to the production or deposition of this protein by the AM fungi in plantations and in non-forested areas.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Another benefit attributed to 'glomalin' is soil carbon deposition and subsequent sequestration. Glomalin-related SPs are thought to represent c. 20% of the soil organic carbon and aid carbon sequestration by stabilising soil aggregates (Preger et al, 2007;Rotter et al, 2017;Singh et al, 2020). Some studies have reported that glomalin-related SPs are more recalcitrant than other forms of soil organic matter, including general AMF necromass, but the reason for this is unexplored (Rillig et al, 2001;Preger et al, 2007;Zhang et al, 2017).…”
Section: Glomalin-related Sp Extracts Contain a Complex Mixture Of Substancesmentioning
confidence: 99%
“…Meanwhile, GRSP is an important cementing agent in the formation of soil aggregates, which plays a major role in maintaining soil organic carbon (SOC) pool (Rillig et al, 2001;Wright et al, 2007), which contributed to SOC accumulation with more than 20 times higher than microbial biomass (Rillig et al, 2001;Godbold et al, 2006;Prescott, 2010;Guo, 2013). In addition, GRSP is one of the indicators of active nitrogen along with SOC (Rotter et al, 2017). The GRSP in soil is classified into the total GRSP (TG) and the easily extracted GRSP (EEG) based on the different extracted methods (Wright et al, 1998b;Rillig et al, 2001).…”
Section: Introductionmentioning
confidence: 99%